Deep Brain Stimulation: Are Astrocytes a Key Driver Behind the Scene?. (24th January 2014) - Fenoy, Albert J.; Goetz, Laurent; Chabardès, Stéphan; Xia, Ying
Summary Despite its widespread use, the underlying mechanism of deep brain stimulation (DBS) remains unknown. Once thought to impart a "functional inactivation", there is now increasing evidence showing that DBS actually can both inhibit neurons and activate axons, generating a wide range of effects. This implies that the mechanisms that underlie DBS work not only locally but also at the network level. Therefore, not only may DBS induce membrane or synaptic plastic changes in neurons over a wide network, but it may also trigger cellular and molecular changes in other cells, especially astrocytes, where, together, the glial–neuronal interactions may explain effects that are not clearly rationalized by simple activation/inhibition theories alone. Recent studies suggest that (1) high‐frequency stimulation (HFS) activates astrocytes and leads to the release of gliotransmitters that can regulate surrounding neurons at the synapse; (2) activated astrocytes modulate synaptic activity and increase axonal activation; (3) activated astrocytes can signal further astrocytes across large networks, contributing to observed network effects induced by DBS; (4) activated astrocytes can help explain the disparate effects of activation and inhibition induced by HFS at different sites; (5) astrocytes contribute to synaptic plasticity through long‐term potentiation (LTP) and depression (LTD), possibly helping to mediate the long‐term effects of DBS; and (6) DBS may increase delta‐opioid receptor activity in astrcoytes to confer neuroprotection. Together, the plastic changes in these glial–neuronal interactions network‐wide likely underlie the range of effects seen, from the variable temporal latencies to observed effect to global activation patterns. This article reviews recent research progress in the literature on how astrocytes play a key role in DBS efficacy.